Republic of Mozambique : Poverty Reduction Strategy Paper-Progress Report. (IMF Staff Country Reports; Country Report ;, 2014)
This chapter discusses key findings of the Poverty Reduction Strategy Paper progress report on the Republic of Mozambique. The monitoring of 62 output indicators of the 2013 Plano Economico e Social showed that 44 percent of the indicators have achieved the planned targets, 50 percent have not attained the targets but have made significant progress, and the remaining 6 percent of the indicators are lagging far behind. In terms of objectives, the human development objective is showing the best performance, whereas promotion of employment still has challenges and constraints to overcome in fulfilling its targets.